Securing transmissions by friendly jamming scheme in wireless networks - Li, Guangshun; Sheng, Xiaofei; Wu, Junhua; Yu, Haili (Journal of parallel and distributed computing, 2020)
In this paper, we focus on the design of optimal relay and jammer selection strategy in relay-aided wireless networks. Different from previous works, assuming that the channel state information (CSI) of illegitimate nodes was available and only an eavesdropper existed, we first analyze disadvantages of joint relay and jammer selection (JRJS), average optimal relay selection (AORS), traditional maximum relay selection (TMRS) schemes. Then, we design an optimal relay and jammer selection strategy where the ratio of received SNRs at the destination generated by any two relays is maximized. By applying proposed strategy, computation complexity can be reduced. Moreover, we derive the lower and upper bounds of the secrecy outage probability based on the assumptions of existence of only illegitimate node and symmetric case for mathematical convenience. Finally, simulation shows that the proposed strategy operating with no CSI of illegitimate nodes can work efficiently compared with JRJS, TMRS and AORS strategies. •Optimal relay and jammer.•Transmission reliability.•Security performance.